2016
DOI: 10.1186/s40621-016-0067-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with legal interventions

Abstract: BackgroundCurrent research regarding injuries caused during interactions between police officers and civilians is conducted intermittently or on a very narrow sample frame which provides very little clinical information about the injuries suffered or the adverse outcomes. The aim of this study is to identify comorbid risk factors and describe acute outcomes of medically treated traumatic injuries occurring as a result of contact with law enforcement personnel.MethodsFor this retrospective study, patients injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 11 publications
1
17
0
2
Order By: Relevance
“…[6][7][8] Still, others have produced analyses of existing injury and mortality data derived from hospital records and death certificates. [9][10][11] Researchers have yet to answer basic epidemiological questions about police violence, however, such as whether the incidence rate of injuries caused by US police has changed over time, or the degree to which these injuries are properly coded as Blegal intervention^(i.e., those caused by law enforcement, as per the International Classification of Diseases (ICD)) and are therefore identifiable in statistical analyses of hospital data. Additionally, little attention has been paid to the role of private security guards in use-of-force incidents, even as the private security industry has grown steadily since 2001, and the number of private guards in the USA has come to be roughly equal to the number of police officers.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Still, others have produced analyses of existing injury and mortality data derived from hospital records and death certificates. [9][10][11] Researchers have yet to answer basic epidemiological questions about police violence, however, such as whether the incidence rate of injuries caused by US police has changed over time, or the degree to which these injuries are properly coded as Blegal intervention^(i.e., those caused by law enforcement, as per the International Classification of Diseases (ICD)) and are therefore identifiable in statistical analyses of hospital data. Additionally, little attention has been paid to the role of private security guards in use-of-force incidents, even as the private security industry has grown steadily since 2001, and the number of private guards in the USA has come to be roughly equal to the number of police officers.…”
Section: Introductionmentioning
confidence: 99%
“…Police officers may be less prone to use force against arrested children than against older individuals. In the USA, it was reported that patients injured from legal interventions were less likely to be children than adolescents or adults . The causes of injuries among children were three times less often legal interventions than they were general assaults …”
Section: Discussionmentioning
confidence: 99%
“…In the USA, it was reported that patients injured from legal interventions were less likely to be children than adolescents or adults. 22 The causes of injuries among children were three times less often legal interventions than they were general assaults. 22 The medical histories of the arrested children in this study were unremarkable in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…Eine komorbide Störung durch Substanzgebrauch erhöht das Risiko zusätzlich [13,14]. Vermutlich leidet auch ein erheblicher Teil der Personen, die durch polizeiliche Maßnahmen verletzt werden, an einer psychischen Erkrankung, was wiederum das Risiko einer zusätzlichen Traumatisierung erhöht [15]. In Deutschland war ein Drittel der zwischen 2007 und 2014 durch die Polizei erschossenen Personen psychisch erkrankt [16].…”
Section: Conclusion Police Training Programs Should Focus On In-unclassified